Designing a Structural Model of Talent Management Based on Good Governance in the Sports Organization - Doosti Shakib, Marjan; Amirkabiri, Alireza; Haghshenas Kashani, Farideh (Future of Work and Digital Management Journal, 2026)
Talent management is a set of integrated human resource processes that function beyond the boundaries of individual HR practices. A talent management strategy requires a comprehensive perspective on these processes. The present study aimed to design a structural model of talent management based on good governance in the sports organization. This research, in terms of purpose, is exploratory and, in terms of application, is applied. The methodology adopted is a combination of qualitative and quantitative approaches. In the qualitative phase, thematic analysis and open, axial, and selective coding were applied. In the quantitative phase, structural equation modeling (SEM) was used to evaluate the research model and examine the relationships among the designed questions and model categories. The statistical population in the qualitative part consisted of 15 senior managers of the sports organization in Tehran, who were considered experts for the qualitative stage. In the quantitative part, the population included 200 middle managers and experts from the sports organization in Tehran. Using the Krejcie and Morgan table, 127 participants were selected as the statistical sample. The data collection tool in the qualitative phase was semi-structured interviews, designed based on the components of the paradigmatic model. In the quantitative phase, a 57-item questionnaire was developed, derived from the conceptual model formed in the interview stage. To assess reliability in the qualitative phase, the test–retest method was applied. For the quantitative phase, Cronbach’s alpha coefficient was used to determine the reliability of the questionnaire; the alpha coefficient for all variables exceeded 0.70, indicating acceptable reliability. In the quantitative analysis, SEM was employed, and all computations were performed using SmartPLS software. The findings revealed that the main components of the structural model of talent management based on good governance in the sports organization include: managing generational differences based on good governance, sustainability of talent management based on good governance, talent identification based on good governance, talent acquisition based on good governance, talent development and empowerment based on good governance, talent retention based on good governance, and talent management performance evaluation based on good governance. Moreover, the resulting model demonstrated appropriate validity.